2015
DOI: 10.1371/journal.pone.0117930
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wrist Angle on Median Nerve Appearance at the Proximal Carpal Tunnel

Abstract: This study investigated the effects of wrist angle, sex, and handedness on the changes in the median nerve cross-sectional area (MNCSA) and median nerve diameters, namely longitudinal diameter (D1) and vertical diameter (D2). Ultrasound examination was conducted to examine the median nerve at the proximal carpal tunnel in both dominant and nondominant hands of men (n = 27) and women (n = 26). A total of seven wrist angles were examined: neutral; 15°, 30°, and 45° extension; and 15°, 30°, and 45° flexion. Our r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 42 publications
9
42
2
Order By: Relevance
“…The deformity of the median nerve during wrist flexion or extension has already been shown and the CSA of the median nerve has been reported to decrease during wrist motion [5]. Also, the acute postural changes of the wrist have been reported to increase the median nerve stiffness [3].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The deformity of the median nerve during wrist flexion or extension has already been shown and the CSA of the median nerve has been reported to decrease during wrist motion [5]. Also, the acute postural changes of the wrist have been reported to increase the median nerve stiffness [3].…”
Section: Discussionmentioning
confidence: 95%
“…A recently published study showed that posture-induced changes could be detected by Shear-Wave Elastography (SWE) at the median nerve [3]. Previous US studies have reported conflicting results on whether median nerve cross-sectional area (CSA) is altered in different wrist postures [4][5][6]. Although the effect of acute postural changes to the median nerve has been studied, the chronic effects of postural changes to the median nerve have not been clearly identified yet.…”
Section: Introductionmentioning
confidence: 99%
“…22 , 24 - 26) Therefore, the irregular shape of the median nerve is influenced by compression stress from surrounding finger flexor tendons within the carpal tunnel. The changes in the MNCSA in the typing I and typing II conditions may suggest an observable proportionate change in the median nerve diameter over typing time.…”
Section: Discussionmentioning
confidence: 99%
“…Wrist angle changes are known to cause compression stress on the median nerve and lead to deformation of the median nerve at the carpal tunnel region (Loh & Muraki, 2014;Wang et al, 2014). In addition, finger movement also causes deformation of the median nerve, due to the compression from the surrounding soft tissues and the finger flexor tendon (Korstanje et al, 2010;Kursa et al, 2006;Loh et al, 2016a;Loh et al, 2016b;Ugbolue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%